THE USE OF THE WORDWALL GAME FOR PROMOTING VOCABULARY BUILDING IN INDONESIAN YOUNG LEARNERS EFL CLASSROOM - Maulya, Dhini Erda (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study looks at how the Wordwall digital game media can be used to improve vocabulary knowledge and pronunciation in EFL classes for young Indonesian learners. Using a qualitative approach, the study analyzed students' and teachers' experiences and perceptions of using Wordwall as a vocabulary learning resource. The study consisted of five class meetings with students aged 9 to 10 years old. Classroom observations, semi-structured interviews, and reflective journals were used to collect data. Findings showed that the Wordwall game significantly increased students' motivation and engagement in vocabulary learning, with the visual element particularly aiding retention. However, technical challenges such as limited device access and internet connectivity were barriers to implementation. Teachers reported improved interactivity in the classroom and increased student participation, while noting the need for better infrastructure and technological support. This study shows that while Wordwall offers promising potential for vocabulary instruction, successful implementation requires careful consideration of technical resources, teacher training, and student support systems.